2018
DOI: 10.1177/2050640618798508
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk perception in relation to associated symptoms in Barrett's patients: A cross sectional study on quality of life

Abstract: Background: Barrett's oesophagus affects patients' quality of life and may be a psychological burden due to the threat of developing an oesophageal adenocarcinoma. Objective: Assessing the oesophageal adenocarcinoma risk perceived by non-dysplastic Barrett's oesophagus patients and its association with quality of life, illness perception and reflux symptoms. Methods: This cross-sectional questionnaire study included 158 Barrett's oesophagus non-dysplastic patients aged 18-75 years. Based on their annual and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
6
11
1
Order By: Relevance
“…Another factor increasing fear of cancer was the presence of EAC in family or friends. This finding seems consistent with our previous study, in which we found that the presence of cancer in family or friends was associated with overestimating one's own risk of developing EAC [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another factor increasing fear of cancer was the presence of EAC in family or friends. This finding seems consistent with our previous study, in which we found that the presence of cancer in family or friends was associated with overestimating one's own risk of developing EAC [15].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the literature [4,[8][9][10]15,18], the present study found that although a minority of patients (discussed more in the DBEp than NDBEp) mentioned that fear of cancer had a daily impact on their quality of life, all patients agreed that experiencing symptoms increased thoughts of developing cancer. Another factor increasing fear of cancer was the presence of EAC in family or friends.…”
Section: Discussionsupporting
confidence: 90%
“…9 Our recent study, performed in a Dutch single center, showed decreased HRQoL in those patients who overestimated their cancer risk. 6 Most BE patients reported a HRQoL compared to a general Dutch population, this in contrast to the results on HRQoL in previous studies. 10 Many of these studies are underpowered, single center or cannot be reliably compared with current patient pathways.…”
Section: Introductioncontrasting
confidence: 85%
“…5 Previous studies have shown it is difficult for patients to accurately estimate this cancer risk. [6][7][8] These perceptions on developing EAC may affect patients' HRQoL. HRQoL is generally considered encompassing patients' physical-, psychological-, and social functioning, which can be affected by both the disease and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…With a reported 30–125-fold relative risk of the lethal esophageal adenocarcinoma (EAC) ( 3 ), the incidence of BE has increased dramatically in the past 40–50 years, despite controlling for increased endoscopy rates ( 4 6 ). Patient quality of life suffers significantly because of BE-associated symptoms, which include regurgitation, difficulty swallowing, heartburn, chest pain, and justifiable fear of progression to cancer ( 7 ). Although the risk factors such as male sex, being non-Hispanic White, symptomatic gastroesophageal reflux disease (GERD), smoking, central obesity, physical activity, and alcohol intake for BE have been extensively investigated ( 8 ), the exact cause of BE is still unknown.…”
Section: Introductionmentioning
confidence: 99%